Characteristics and outcomes of COVID-19 patients hospitalized at a Central Hospital in Harare, 2020-2022 - Linda Nyasha Kanzara; Isaac Phiri; Hamufare Dumisani Mugauri; Addmore Chadambuka; Tsitsi Patience Juru; Gerald Shambira; Notion Tafara Gombe; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health, 2025)
Introduction: In June 2021, Zimbabwe experienced a third COVID-19 wave characterized by a 3.5% case fatality rate compared to 1.5% in the first wave and 2.6% in the second wave. Sixty-eight percent of these deaths were among hospitalized patients. We investigated the characteristics and outcomes of hospitalized COVID-19 patients at a central hospital in Harare from 2020 to 2022. The findings are critical in informing strategies for managing future epidemics and public health threats in the country.